BIBLIOTECILE PUBLICE DIN REPUBLICA MOLDOVA: DINAMICA ACTIVITĂŢII ÎN ANII 2008-2012 - OSOIANU, director adjunct, Biblioteca Naţională a Republicii Moldova, Vera (BIBLIOPOLIS, 2020)
The study emphasizes the activity dynamics of public libraries during the last years and practically represents a continuation of a similar study realized in 2008. The analysis of the dynamics of human resources, collections, spaces, endowment with modern information and communicative technologies demonstrates that public libraries didn’t pass the period of stagnation, extending over many years. The study about libraries, realized on the basis of the most important indicators of performance, are strong argument in this sense: 8 libraries maintained their top position and just 2 have given way to other libraries. The examination is reserved for continuous professional training is very serious problem the solving of which depends, mostly, of the changing of librarian area.